Chromium Oxide Tetrafluoride and Its Reactions with Xenon Hexafluoride; the [XeF5]+ and [Xe2F11]+ Salts of the [CrVIOF5]−, [CrVOF5]2−, [CrV2O2F8]2−, and [CrIVF6]2− Anions. Issue 69 (14th November 2019) - Goettel, James T.; Bortolus, Mark R.; Stuart, Daniel G.; Mercier, Hélène P. A.; Schrobilgen, Gary J.
Abstract: Molten mixtures of XeF6 and Cr VI OF4 react by means of F2 elimination to form [XeF5 ][Xe2 F11 ][Cr V OF5 ]⋅ 2 Cr VI OF4, [XeF5 ]2 [Cr IV F6 ]⋅ 2 Cr VI OF4, [Xe2 F11 ]2 [Cr IV F6 ], and [XeF5 ]2 [Cr V 2 O2 F8 ], whereas their reactions in anhydrous hydrogen fluoride (aHF) and CFCl3 /aHF yield [XeF5 ]2 [Cr V 2 O2 F8 ]⋅ 2 HF and [XeF5 ]2 [Cr V 2 O2 F8 ]⋅ 2 XeOF4 . Other than [Xe2 F11 ][M VI OF5 ] and [XeF5 ][M VI 2 O2 F9 ] (M=Mo or W), these salts are the only Group 6 oxyfluoro‐anions known to stabilize noble‐gas cations. Their reaction pathways involve redox transformations that give [XeF5 ] + and/or [Xe2 F11 ] + salts of the known [Cr V OF5 ] 2− and [Cr IV F6 ] 2− anions, and the novel [Cr V 2 O2 F8 ] 2− anion. A low‐temperature Raman spectroscopic study of an equimolar mixture of solid XeF6 and CrOF4 revealed that [Xe2 F11 ][Cr VI OF5 ] is formed as a reaction intermediate. The salts were structurally characterized by LT single‐crystal X‐ray diffraction and LT Raman spectroscopy, and provide the first structural characterizations of the [Cr V OF5 ] 2− and [Cr V 2 O2 F8 ] 2− anions, where [Cr V 2 O2 F8 ] 2− represents a new structural motif among the known oxyfluoro‐anions of Group 6. The X‐ray structures show that [XeF5 ] + and [Xe2 F11 ] + form ion pairs with their respective anions by means of Xe‐ ‐ ‐F–Cr bridges. Quantum‐chemical calculations were carried out to obtain the energy‐minimized, gas‐phase geometries and the vibrational frequencies of the anions and their ion pairs and to aid in the assignments of their Raman spectra. Abstract : XeF6 and Cr VI OF4 react in melts and in oxidatively resistant solvents to form rare examples of noble‐gas cation salts stabilized by the known [Cr VI OF5 ] −, [Cr IV F6 ] 2−, and [Cr V OF5 ] 2− anions, and the novel [Cr V 2 O2 F8 ] 2− anion. Their [XeF5 ] + and [Xe2 F11 ] + salts were characterized by single‐crystal XRD and/or Raman spectroscopy and provide the first structural characterizations of [Cr V OF5 ] 2− and [Cr V 2 O2 F8 ] 2− (see figure).